An approach to Islamic consumerism and its implications on marketing mix - Haque, A. K. M. Ahasanul; Shafiq, Ali; Maulan, Suharni (IIUM Press, 2017)
This paper discusses consumerism movement from the Islamic point of view, which implies that all the marketing activities should be done in order to satisfy the consumers while adhering to the tenets of Islamic ethical system. In line with this, the paper then discusses the significance and practicality of Islamic marketing and how the traditional marketing mix can be translated into the Islamic marketing mix. Specific elements of the marketing mix are discussed in light of Islamic injunctions. MaqÉsid al-Shari’Éh (Shariah-based objective), Qawa’id Al-Fiqhiya (Islamic legal maxims/principles) and Usul Al-Fiqh (Islamic scholars’ judgments) are the main sources to approach the Islamic consumerism and its implementations on marketing mix, where these sources help find consumers’ rights that could show ways of marketing mix or program of product, price, place, promotion and people. This theoretical paper that holds both academic and practical significance for the need of Islamic marketing is eminent to gain a firm foothold in Muslim markets.